2009
DOI: 10.2478/v10009-009-0012-x
|View full text |Cite
|
Sign up to set email alerts
|

The use of benthic diatoms in estimating water quality of variously polluted rivers

Abstract: Two rivers situated in Central Poland, the Bzura and the Pilica, were selected for analysis of their water quality using benthic diatom species as indicators. The Bzura River has previously been strongly contaminated with organic pollutants, while the Pilica River has been classified as having good water quality. Samples were collected from nine sites along the Bzura in April 2003 and seven sites along the Pilica in April 2006. The main aims of the study were to determine the dominant diatom species present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 2 publications
(3 reference statements)
2
37
0
1
Order By: Relevance
“…Palmer (1969) reported that N. palea was the diatom species most tolerant of organic pollution. Similar reports on N. palea were noted by a number of researchers (Gómez and Licursi 2001, Soininen 2002, Bellinger et al 2006, Szczepocka and Szulc 2009). This species is also commonly found in polluted Turkish rivers (Gürbüz and Kivrak 2002, Dere et al 2006, Kalyoncu et al 2009, Solak 2011.…”
Section: Discussionsupporting
confidence: 87%
“…Palmer (1969) reported that N. palea was the diatom species most tolerant of organic pollution. Similar reports on N. palea were noted by a number of researchers (Gómez and Licursi 2001, Soininen 2002, Bellinger et al 2006, Szczepocka and Szulc 2009). This species is also commonly found in polluted Turkish rivers (Gürbüz and Kivrak 2002, Dere et al 2006, Kalyoncu et al 2009, Solak 2011.…”
Section: Discussionsupporting
confidence: 87%
“…This rating corresponds with the analysis of the physicochemical parameters of water in this river (Szczepocka & Szulc 2009, Szulc 2009). Descy and Ector (1996) have proposed a range of values for dividing the BDI into corresponding classes used to assess the ecological status of a body of water.…”
Section: According To the Requirements Of The Water Framework Directimentioning
confidence: 66%
“…Previous research in Poland primarily used the SPI and GDI (Zgrundo & Bogaczewicz-Adamczak 2004, Szczepocka & Szulc 2009). The BDI has never been applied in Poland so there have been no attempts to adjust the ranges of values for this index, as have been done for the SPI and GDI (Dumnicka et al 2006, modified).…”
Section: According To the Requirements Of The Water Framework Directimentioning
confidence: 99%
“…Moreover, IPS and GDI were in the group of indices proposed for the assessment the quality of water of the Gulf of Gdansk (Bogaczewicz-Adamczak, Dziengo 2003; Zgrundo 2004). They were also used in the water quality assessment in two rivers in Central Poland: Bzura and Pilica (Szczepocka, Szulc 2009;Rakowska, Szczepocka 2011).…”
Section: Discussionmentioning
confidence: 99%